International extradition : United States law and practice - Bassiouni, M. Cherif, 1937-2017 (Oxford University Press, 2014)
This comprehensive guide covers all aspects of extradition to and from the United States, while making critical, theoretical, and practical evaluations of these aspects, and proposing alternatives. The rights of individuals, balancing of states interests, and preservation of world order within the Rule of Law form the conceptual framework of this book. The focus within U.S. practice explores the essentials involved in the executive branches treaty-making power, as implemented through its foreign relations practice, and as scrutinized by the judiciary. The Sixth Edition updates the treaties, la.